Diese Seite drucken

Ableitungsregeln

Ableiten von x
Ableiten von x (f(x) ---> f'(x) = 1)

 

Ableiten einer Konstanten
Ableiten einer Konstanten (f(x) = 3 ---> f'(x) = 0)

 

Faktorregel
Ableitung - Faktorregel

 

Summenregel
Ableitung - Summenregel

 

Differenzregel
Ableitung - Differenzregel

 

Produktregel
Ableitung - Produktregel

 

Quotientenregel
Ableitung - Quotientenregel

 

Potenzenregel
Ableitung - Potenzregel

 

Kettenregel
Ableitung - Kettenregel

 

Standard Funktionsableitungen ... 

Ableitung Wurzel
f(x) = √x   --->   f'(x) = 1 / 2√x

Ableitung e-Funktion:
f(x) = e^x   --->   f'(x) = e^x

Ableitung Logarithmusfunktion:
f(x) = ln(x)   --->   f'(x) = 1 / x

Ableitung Potenzfunktion:
f(x) = x^2   --->   f'(x) = 2x

Ableitung Sinusfunktion:
f(x) = sin(x)   --->   f'(x) = cos(x)

Ableitung Cosinusfunktion:
f(x) = cos(x)   --->   f'(x) = -sin(x)

Ableitung Tangensfunktion:
f(x) = tan(x)   --->   f'(x) = 1 / cos^2(x)